1995
DOI: 10.1095/biolreprod53.5.1066
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Oviductal Sperm Reservoir in Cattle1

Abstract: A reservoir for sperm has been found in the oviductal isthmus in several species. Sperm are apparently trapped in the reservoir by binding to the oviductal epithelium, although other factors may be involved. We hypothesized that binding sites for bovine sperm are limited to the isthmus and are regulated by the hormonal state of the cow. Ipsilateral oviducts were obtained from heifers that were preovulatory (in estrus), had ovulated recently (within 12 h), or were in diestrus (Day 10). The isthmic and the ampul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
106
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 50 publications
8
106
1
1
Order By: Relevance
“…In contrast to previous results in pigs [11] and cows [52], we found preferential binding of caudal spermatozoa to the isthmus but not ampulla of follicular-phase sows compared to non-cycling gilts. This is consistent with studies in the horse [53] in which the presence of oestrus (but not diestrus) concentrations of steroids in the medium increased the percentage of spermatozoa attaching to both the isthmus and ampulla of the oviduct.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous results in pigs [11] and cows [52], we found preferential binding of caudal spermatozoa to the isthmus but not ampulla of follicular-phase sows compared to non-cycling gilts. This is consistent with studies in the horse [53] in which the presence of oestrus (but not diestrus) concentrations of steroids in the medium increased the percentage of spermatozoa attaching to both the isthmus and ampulla of the oviduct.…”
Section: Discussioncontrasting
confidence: 99%
“…The reason for this may be attributed to differences in the epithelial structure, regional secretions and biochemical features that exist between the isthmus and ampulla. Studies report no differences in the binding capacity of spermatozoa to the isthmus and ampulla of pigs [11,51] or cattle [52], although Raychoudhury and Suarez [55] found more porcine spermatozoa bound to the isthmus (10.8 ± 0.4 spermatozoa per 0.3 mm 2 ) than to the ampulla (5.6 ± 0.4 spermatozoa per 0.3 mm 2 ).…”
Section: Discussionmentioning
confidence: 95%
“…Another possibility is that AEA, as a second messenger, might mediate the effect of other molecules, such as sulfated glycoconjugates, in the oviductal fluid and be involved in sperm releasing signaling pathways at the time of fertilization. To date, it has been shown that sulfated glycoconjugates (Bosch et al et al 2006) also promote sperm release from oviductal reservoirs and that changes in oviduct mucosa do not participate in this mechanism (Lefebvre et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In a number of mammals, sperm are stored for several hours in an oviductal reservoir, in which sperm are bound tightly to the epithelium of the oviduct (e.g., Suarez and Osman 1987). Carbohydrates mediate the adherence of sperm to the epithelium, with different sugars playing important roles in different species (e.g., Demott et al 1995;Lefebvre et al 1995Lefebvre et al , 1997Ekhlasi-Hundrieser et al 2005). In cows, for example, biochemical studies suggest that fucose residues on oviductal annexins act as receptors for sperm, with several sperm-bound seminal proteins recognizing the fucose moiety (Ignotz et al 2001(Ignotz et al , 2007Gwathmey et al 2006).…”
mentioning
confidence: 99%